Elasto-plastic solution for undrained cylindrical cavity expansion in refuse soil - Weimin Zhang; Fengwei Guo; Yun Zhao (Scientific Reports)
Abstract To address geotechnical engineering issues such as pile driving, lateral pressure tests, and static cone penetration tests on increasing number of infrastructure projects being constructed on landfills, an elasto-plastic theoretical solution for the undrained cylindrical cavity expansion in refuse soil is proposed in this paper based on an elasto-plastic constitutive model for refuse soil considering the reinforcement effect of fibers, along with a large deformation theory. The correctness of the results is validated through comparison with existing solutions based on the modified Cam-clay model. The results indicate that the response of columnar pore expansion in refuse soil is significantly different from that in ordinary soil. Near the pore, refuse soil does not enter a critical state, only the slurry-like components do. Subsequently, the reinforcement effect of the fiber material begins to manifest. Refuse soils with different fiber contents undergo both elastic and plastic stages before reaching the critical state line of the slurry-like components in the soil. They then move a certain distance along this line to reach a maximum. Given the rarity of engineering construction on similar sites in the past, the unique response of refuse soil during cylindrical cavity expansion should be given special attention.